Ethnoecology of Madura Farmers in Managing Peatlands in Malikian Village, Mempawah Hilir District, Mempawah Regency - Prasetio, Muhammad Adi; Fatmawati, Fatmawati; Sudirman, Sudirman; Arkan, Herlan; Musa, Dahniar Th.; Winarno, Bondan; Novita, Nisa (Riviera Publishing, 2026)
Peatlands are vulnerable ecosystems that require sustainable management patterns based on local wisdom. Madura farmers in Malikian Village, Mempawah Hilir District, Mempawah Regency have ethnoecological knowledge that has been passed down from generation to generation in managing peatlands. This study aims to analyze the form of ethnoecological knowledge of Madura farmers and the peatland management practices they implement. The research uses a qualitative approach with ethnographic methods. Data were collected through field observations, in-depth interviews, and documentation, then analyzed using an interpretive descriptive approach. The results show that Madura farmers apply the principle of natural balance, selection of planting time based on natural signs, traditional soil cultivation techniques, and adaptive water control suited to peat characteristics. The discussion emphasizes that these ethnoecological practices contribute to maintaining soil fertility and minimizing damage to peat ecosystems. This study concludes that the ethnoecological knowledge of Madura farmers plays an important role as the basis for sustainable peatland management that is relevant for development in environmental management policies